Diabetes in America : a geographic & demographic analysis of an epidemic by state and congressional district - Mars, Laura (Health in America series., 2013)
"The first volume in the new series Health in America, this resource examines diabetes nationally and in each state, US territory, and congressional district. It lists statistics on total number of diabetics, prevalence (with color maps), percent of uninsured diabetics, number of hospitalizations and emergency room visits, annual hospitalization costs, annual total medical costs, and percent of diabetics with HbA1c above 7 (high blood sugar levels), further broken down by gender, race/ethnicity, and age. A final section includes state rankings for these categories by overall numbers, gender, race/ethnicity, and age, and comparative statistics. Contact information for politicians in each district is included. Data has been culled from the National Minority Quality Forum. Available online are sortable ranking tables for all topics and access to rankings for all 441 congressional districts, instead of just the top and bottom 50 for each data point in the book"--The Free Library.